2006
DOI: 10.1007/s10519-006-9046-y
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Transgenic Mice Expressing Human Cystathionine Beta-Synthase to Study Down Syndrome

Abstract: Down syndrome (DS) is the most common genetic cause of significant cognitive disability. We hypothesize that by identifying metabolic alterations associated with cognitive impairment, it may be possible to develop medical or dietary interventions to ameliorate cognitive disabilities in persons with DS. Evidence suggests that one-carbon/transsulfuration (1C-TS) metabolism is abnormal in persons with DS. Cystathionine beta-synthase (CBS) plays a critical role in this metabolic system. The gene for CBS is on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…On the other hand, CBS is a key enzyme in the homocysteine to cystathionine transsulfuration step that plays a critical role in linking the folate and methionine cycles and in regulating homocysteine levels [6]. Recent evidence has demonstrated that CBS 844ins68 has no statistically significant effects on homocysteine and folate concentrations, but it appears to counterbalance the homocysteine-raising and folate-lowering effects of the MTHFR 677TT genotype, making it similar to that observed in MTHFR 677CT or CC individuals [26].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, CBS is a key enzyme in the homocysteine to cystathionine transsulfuration step that plays a critical role in linking the folate and methionine cycles and in regulating homocysteine levels [6]. Recent evidence has demonstrated that CBS 844ins68 has no statistically significant effects on homocysteine and folate concentrations, but it appears to counterbalance the homocysteine-raising and folate-lowering effects of the MTHFR 677TT genotype, making it similar to that observed in MTHFR 677CT or CC individuals [26].…”
Section: Discussionmentioning
confidence: 97%
“…Functional regeneration of this methionine synthase requires the participation of another enzyme, methionine synthase reductase, which is encoded by the MTRR gene [23]. Cystathioninebeta-synthase (CBS) acts in the transulfuration of homocysteine to cystathionine, playing a critical role in linking the folate and methionine cycles in regulating homocysteine levels [9]. Another important protein involved in this metabolism is folate-transporting protein (RFC-1), transporting 5-methyltetrahydrofolateinto the cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mice carrying the hRFC gene were produced from FVB mice using this fragment as described previously (Butler et al, 2006). Transgenic mice were genotyped by PCR.…”
Section: Mouse Husbandrymentioning
confidence: 99%
“…To determine the number of integration sites of the transgene and to verify that the hRFC transgene had not integrated into mouse chromosome 10 (the location of the mRFC gene), metaphase spreads were prepared from transgenic mouse spleens and analyzed by FISH as described previously (Butler et al, 2006).…”
Section: Mouse Husbandrymentioning
confidence: 99%
See 1 more Smart Citation